2020
DOI: 10.1111/rec.13301
|View full text |Cite
|
Sign up to set email alerts
|

Once a pond in time: employing palaeoecology to inform farmland pond restoration

Abstract: The restoration of highly terrestrialized farmland ponds that combines the removal of woody vegetation and pond sediment greatly enhances aquatic biodiversity. Nonetheless, questions remain regarding the historical precedent of pond restoration, and particularly if post‐restoration aquatic macrophyte communities resemble pre‐terrestrialization assemblages. We used a paleoecological approach to address these questions for a typical, recently restored farmland pond in Norfolk, eastern England. Plant and animal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Although the effect of management was not examined in this study, management was considered to be necessary for the following reasons: (1) Woody plants gradually invaded the inner area of the ponds as part of the terrestrialization process. Shallow farm ponds without management can be fully terrestrialized in 20–30 years (Walton et al 2021); (2) Species diversity began to decrease after 1–4 years of construction. In addition, in the fifth year, the number of species in the experimental ponds decreased to below the regularly managed reference pond; (3) The percent vegetation cover in the ponds increased to 93% compared to 45% in the reference pond.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effect of management was not examined in this study, management was considered to be necessary for the following reasons: (1) Woody plants gradually invaded the inner area of the ponds as part of the terrestrialization process. Shallow farm ponds without management can be fully terrestrialized in 20–30 years (Walton et al 2021); (2) Species diversity began to decrease after 1–4 years of construction. In addition, in the fifth year, the number of species in the experimental ponds decreased to below the regularly managed reference pond; (3) The percent vegetation cover in the ponds increased to 93% compared to 45% in the reference pond.…”
Section: Discussionmentioning
confidence: 99%
“…Although rapid vegetation establishment in farm ponds has been reported in some studies (Matthews & Endress 2010; Walton et al 2021), the net effect of planting in newly constructed farm ponds has not been fully evaluated yet. This study showed that fertile conditions and abundant seed sources allowed vegetation to establish quickly in farm ponds without planting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there are significant knowledge gaps regarding the long-term dynamics and patterns in pond environments, biological diversity, and functioning. As for larger lentic water bodies, paleoecological approaches could provide critical information for inferring long-term (c.100s-1000s years) changes in pond ecology in response to environmental change and, in turn, inform restoration strategies (Walton et al 2021). This is of particular importance for demonstrating the scope for returning communities to those recorded prior to major human impacts.…”
Section: Global and Long-term Datamentioning
confidence: 99%
“…Furthermore, UK farmland ponds are widely threatened by terrestrialization, resulting in the overwhelming numerical dominance of late-successional ponds with high canopy shading and lowered species diversity at pond and pond-landscape scales (Sayer et al, 2013;Sayer & Greaves, 2020). To tackle the problem of terrestrialization, farmland ponds can be restored by active tree and sediment removal, and much recent research shows this approach to be highly effective (Sayer & Greaves, 2020;Walton et al, 2021). This pilot study investigated the potential of ecoacoustic surveys for assessing the success of pond restoration.…”
Section: Introductionmentioning
confidence: 99%